(untitled) (Research, Society and Development, 2021)
Objective: To evaluate the effect of a pain education program associated with exercise therapy in patients who have chronic nonspecific low back pain with and without central sensitization. Methodology: This is a randomized controlled clinical trial, in which patients were divided into two groups: patients with chronic nonspecific low back pain without central sensitization (G1) or patients with nonspecific chronic low back pain with sensitization (G2). After previous assessment of pain intensity, perception of improvement, disability, kinesiophobia, agility and health expenses, patients received treatment for 5 weeks, totaling 10 sessions. Results: The results did not show differences between the groups, but the intragroup comparison showed an improvement in mobility (p=0.005) and pain (p=0.005) and a reduction in disability (p=0.036) and kinesiophobia (p=0.012) for the G1. For G2 there was improvement in mobility (p=0.012), pain (p=0.012) and reduction in disability (p=0.018). The level of physical activity was different only for the group with central sensitization (p=0.034). As for health expenses, it is clear that there were no changes over time, for hospitalizations and expenses with medical appointments, given the short period evaluated. Conclusion: It is concluded that a pain education program combined with exercise is beneficial to improve physical functionality, pain, reduced disability and kinesiophobia for G1, while for G2 there was an improvement in the level of physical activity, mobility, pain and disability reduction. Finally, we hope that this study will contribute to the implementation of more effective care programs and protocols.